2001
DOI: 10.1101/gr.184001
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Experimental Analysis of Microsatellites in Rice (Oryza sativa L.): Frequency, Length Variation, Transposon Associations, and Genetic Marker Potential

Abstract: A total of 57.8 Mb of publicly available rice (Oryza sativa L.) DNA sequence was searched to determine the frequency and distribution of different simple sequence repeats (SSRs) in the genome. SSR loci were categorized into two groups based on the length of the repeat motif. Class I, or hypervariable markers, consisted of SSRs Ն20 bp, and Class II, or potentially variable markers, consisted of SSRs Ն12 bp <20 bp. The occurrence of Class I SSRs in end-sequences of EcoRI-and HindIII-digested BAC clones was one S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

71
1,028
7
11

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,351 publications
(1,131 citation statements)
references
References 52 publications
71
1,028
7
11
Order By: Relevance
“…The contigs ranging from 80 to 530 bp in length were merged, and a total of 10,487,858 contigs were assembled. These contigs were screened using the Simple Sequence Repeat Identification Tool (SSRIT; Temnykh et al., 2001) and at least five di‐, tri‐, tetra‐, penta‐, and hexanucleotide repeats were selected, resulting in a total of 305,556 SSR‐containing sequences.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The contigs ranging from 80 to 530 bp in length were merged, and a total of 10,487,858 contigs were assembled. These contigs were screened using the Simple Sequence Repeat Identification Tool (SSRIT; Temnykh et al., 2001) and at least five di‐, tri‐, tetra‐, penta‐, and hexanucleotide repeats were selected, resulting in a total of 305,556 SSR‐containing sequences.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Additional investigation of O. sativa (TA) n microsatellites indicated that nearly 45% were flanked by sequence that Fig. 2 Putative Ostrinia nubilalis microsatellite-associated interspersed nuclear element (OnMINE-1) secondary structure elements had homology to Micron superfamily members (Temnykh et al 2001). Primate Alu elements also are located near multiple microsatellite repeat motifs (Arcot et al 1995), with the most ancient AluJ class associated with (GAAA) n repeats (Yandava et al 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Genome associations between TEs and microsatellite loci are also observed when integrations occur preferentially into tandem repeats (Akagi et al 2001;Temnykh et al 2001) or when tandem repeats hitchhike within mobile elements (Wilder and Hollocher 2001;López-Giráldez et al 2006;Coates et al 2009). Modification of microsatellite loci by TE insertion has been documented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dataset was divided into small files, each containing 100 FASTA formatted sequences. SSR-containing sequences were identified using SSRIT web based SSR identification tool [46] available at http://www.gramene.org/db/markers/ssrtool. Any sequence was considered as an SSR where a repeat motif of one to six nucleotides in length was repeated at least five times for dinucleotide, trinucleotide, tetranucleotide and pentanucleotide SSRs.…”
Section: Methodsmentioning
confidence: 99%